Differences in the Ability to Write Narrative Texts Using the Wattpad Application Media and Without Using the Wattpad Application Media in Grade VIII Junior High School Students - Dwi Cahyani, Yolanda; Sulastri, Sulastri; Bouakel, Toufik (Cahaya Ilmu Cendekia Publisher, 2024)
Purpose of the study: The purpose of this study was to determine the differences in the ability to write narrative texts using the Wattpad application media and without using the Wattpad application media in class VIII students of State Junior High School 01 North Bengkulu. Methodology: This study used a quantitative experimental method with a sample of 32 students of class VIII of State Junior High School 01 North Bengkulu, selected through purposive sampling. Data were collected through a narrative text writing test assessed based on content, text structure, effective sentences, diction, and spelling. Data analysis used Paired Sample t-Test. Main Findings: The results: (1) the ability to write narrative texts of class VIII students of SMP Negeri 01 Bengkulu Utara using the Wattpad application is in the good category with an average value of 78.8, (2) without using the Wattpad application, students' ability to write narrative texts is in the sufficient category with an average value of 55.0, and (3) there is a significant difference between the two groups. The results of the t-test show \( t_count = 8.048 > t_table = 2.039 \) (p = 0.000 < 0.05), so that the average writing ability with the Wattpad application is higher than without the application. Novelty/Originality of this study: This study offers a new perspective on the effectiveness of digital application media, such as Wattpad, in improving narrative text writing skills among Junior High School students, which has not been widely explored before in the context of Indonesian education.